Incidence and associated risk factors for falls in adults with intellectual disability. Issue 12 (9th September 2019) - Ho, P.; Bulsara, M.; Patman, S.; Downs, J.; Bulsara, C.; Hill, A.‐M.
Abstract: Background: People with intellectual disability (ID) experience age‐related changes earlier in life, and as such, falls among people with ID are of serious concern. Falls can cause injury and consequently reduce quality of life. Limited studies have investigated the incidence of falls among people with ID and the associated risk factors. The purpose of this study was to investigate the incidence of falls and risk factors for falling in people with ID living in the community. Methods: A prospective observational cohort ( n = 78) of community‐dwelling adults with ID. Characteristics measured at baseline included falls history, medication use, balance and mobility. Falls were reported for 6 months using monthly calendars and phone calls. Data were analysed using univariate and multivariate logistic regression to identify risk factors associated with falling. Results: Participants [median (interquartile range) age 49 (43–60) years, female n = 32 (41%)] experienced 296 falls, with 36 (46.2%) participants having one or more falls. The incidence of falls was 5.7 falls (injurious falls = 0.8) per person year (one outlier removed from analysis). A history of falls [adjusted odds ratio (OR): 6.37, 95% confidence interval (CI) (1.90–21.34)] and being ambulant [adjusted OR: 4.50, 95% CI (1.15–17.67)] were associated with a significantly increased risk of falling. Falls were significantly less frequent among participants taking more than four medications [adjusted OR: 0.22, 95% CI (0.06–0.83)] and participants who were continent [adjusted OR: 0.25, 95% CI (0.07–0.91)]. Conclusions: People with ID fall at a younger age compared with the broader community. The associated falls risk factors also differ to older community‐dwelling adults. Health professionals should prioritise assessment and management of falls risk in this population.